Helium isotopes in the Baikal rift underground fluids and its framing (to geodynamics of continental rift genesis). - Polyak, Boris G (PANGAEA, 2000)
Results of studying isotopic composition of helium in underground fluids of the Baikal-Mongolian region during the last quarter of XX century are summarized. Determinations of 3He/4He ratio in 139 samples of gas phase from fluids, collected at 104 points of the Baikal rift zone and adjacent structures are given. 3He/4He values lie within the range from 1x10**-8 (typical for crustal radiogenic helium) to 1.1x10**-5 (close to typical MORB reservoir). Repeated sampling in some points during more than 20 years showed stability of helium isotopic composition in time in each of them at any level of 3He/4He values. There is no systematic differences of 3He/4He in samples from surface water sources and deeper intervals of boreholes in the same areas. Universal relationship between isotopic composition of helium and general composition of gas phase is absent either, but the minimum 3He/4He values occurred in methane gas of hydrocarbon deposits, whereas in nitrogen and carbon dioxide gases of helium composition varied (in the latter maximum 3He/4He values have been measured). According to N2/Ar_atm ratio nitrogen gases are atmospheric. In carbonic gas fN2/fNe ratio indicates presence of excessive (non-atmogenic) nitrogen, but the attitude CO2/3He differs from one in MORB. Comparison of helium isotopic composition with its concentration and composition of the main components of gas phase from fluids shows that it is formed under influence of fractionation of components with different solubility in the gas-water system and generation/consumption of reactive gases in the crust. Structural and tectonic elements of the region differ from the spectrum of 3He/4He values. At the pre-Riphean Siberian Platform the mean 3He/4He = (3.6+/-0.9)x10**- 8 is very close to radiogenic one. In the Paleozoic crust of Khangay 3He/4He = (16.3+/-4.6)x10**-8, and the most probable estimate is (12.3+/-2.9)x10**-8. In structures of the eastern flank of the Baikal rift zone (Khentei, Dauria) affected by the Mz-Kz activization 3He/4He values range from 4.4x10**-8 to 2.14x10**-6 (average 0.94x10**-6). Distribution of 3He/4He values across the strike of the Baikal rift zone indicates advective heat transfer from the mantle not only in the rift zone, but also much further to the east. In fluids of the Baikal rift zone range of 3He/4He values is the widest: from 4x10**-8 to 1.1x10**-5. Their variations along the strike of the rift zone are clearly patterned, namely, decrease of 3He/4He values in both directions from the Tunka depression. Accompanied by decrease in density of conductive heat flow and in size of rift basins, this trend indicates decrease in intensity of advective heat transfer from the mantle to peripheral segments of the rift zone. Comparing this trend with data on other continental rift zones and mid-ocean ridges leads to the conclusion about fundamental differences in mechanisms of interaction between the crust and the mantle in these environments.
(Table 1) Isotopic and geochemical parameters of gas phase from underground fluids of the Baikal rift and its framing
Keywords: Archive of Ocean Data; ARCOD; Area/locality; Argon; Argon-40/Argon-36; Barguzin depression; Bauntovskaya depression; DEPTH, sediment/rock; Gas type; Gobi; Helium; Helium-3/Helium-4; Helium-4/Neon-20; Irkutsk amphitheater; Isotope ratio mass spectrometry; Khangaisk upland; Khentei-Kerulensk zone; Khubsugul depression; Middle Baikal depression; Neon; Nepsky arch; North Baikal depression; North Muisky ridge; Polyak-2000-1; Polyak-2000-10; Polyak-2000-100; Polyak-2000-101; Polyak-2000-102; Polyak-2000-103; Polyak-2000-104; Polyak-2000-105; Polyak-2000-106; Polyak-2000-107; Polyak-2000-108; Polyak-2000-109; Polyak-2000-11; Polyak-2000-110; Polyak-2000-111; Polyak-2000-112; Polyak-2000-113; Polyak-2000-114; Polyak-2000-115; Polyak-2000-116; Polyak-2000-117; Polyak-2000-118; Polyak-2000-119; Polyak-2000-12; Polyak-2000-120; Polyak-2000-121; Polyak-2000-122; Polyak-2000-123; Polyak-2000-124; Polyak-2000-125; Polyak-2000-126; Polyak-2000-127; Polyak-2000-128; Polyak-2000-13; Polyak-2000-14; Polyak-2000-15; Polyak-2000-16; Polyak-2000-17; Polyak-2000-18; Polyak-2000-19; Polyak-2000-2; Polyak-2000-20; Polyak-2000-21; Polyak-2000-22; Polyak-2000-23; Polyak-2000-24; Polyak-2000-25; Polyak-2000-26; Polyak-2000-27; Polyak-2000-28; Polyak-2000-29; Polyak-2000-3; Polyak-2000-30; Polyak-2000-31; Polyak-2000-32; Polyak-2000-33; Polyak-2000-34; Polyak-2000-35; Polyak-2000-36; Polyak-2000-37; Polyak-2000-38; Polyak-2000-39; Polyak-2000-4; Polyak-2000-40; Polyak-2000-41; Polyak-2000-42; Polyak-2000-43; Polyak-2000-44; Polyak-2000-45; Polyak-2000-46; Polyak-2000-47; Polyak-2000-48; Polyak-2000-49; Polyak-2000-5; Polyak-2000-50; Polyak-2000-51; Polyak-2000-52